Microalbuminuria After Kidney Transplantation Predicts Cardiovascular Morbidity - Bielopolski, Dana; Rahamimov, Ruth; Zingerman, Boris; Chagnac, Avry; Azulay-Gitter, Limor; Rozen Zvi, Benaya (Frontiers in Medicine, 2021)
Background: microalbuminuria is a well characterized marker of kidney malfunction, both in diabetic and non-diabetic populations, and is used as a prognostic marker for cardiovascular morbidity and mortality. A few studies implied that it has the same value in kidney transplanted patients, but the information relies on spot or dipstick urine protein evaluations, rather than the gold standard of timed urine collection. Methods: We revisited a cohort of 286 kidney transplanted patients, several years after completing a meticulously timed urine collection and assessed the prevalence of major cardiovascular adverse events (MACE) in relation to albuminuria. Results: During a median follow up of 8.3 years (IQR 6.4-9.1) 144 outcome events occurred in 101 patients. By Kaplan-Meier analysis microalbuminuria was associated with increased rate of CV outcome or death (p=0.03), and this was still significant after stratification according to propensity score quartiles (p=0.048). Time dependent Cox proportional hazard analysis showed independent association between microalbuminuria and CV outcomes two years following microalbuminuria detection (HR 1.83, 95% CI 1.07-2.96). Conclusions: Two years after documenting microalbuminuria in kidney transplanted patients, their CVD risk was increased. There is need for primary prevention strategies in this population and future studies should address the topic.